L’espace de la fantaisie: Prolégomènes à une approche de l’expérience analytique à partir du concept ricœurien d’identité narrative - Amalric, Jean-Luc (B@belonline, 2021)
This article raises the question whether to some extent Ricœur’s theory of narrative identity, read in the light of his philosophy of the imagination, is likely to renew in depth our understanding of analytic experience. In order to do so, it attempts to synthetically retrace the main lines of the interpretation of the Freudian Phantasieren that Ricœur proposes to us, after his Essai sur Freud up to the last articles on psychoanalysis published in Ecrits et Conférences 1. The article shows (a) how the question of productive imagination lies at the heart of Ricœur’s interpretation of psychoanalysis; (b) how it guides his critique of the linguistic interpretation of the unconscious formulated by Lacan and (c) how it leads to a reading of Freudian fantasy in a strongly innovative perspective of a non-linguistic semiotics of the image, attentive to the singularity of analytic experience and capable of projecting a new clarification on the narrative dimension.